A comparative study of two doses of magnesium sulphate in attenuating haemodynamic responses to laryngoscopy and intubation - Kotwani, Manish B.; Kotwani, Deepti M.; Laheri, Vandana (International Journal of Research in Medical Sciences, 2017)
Background: Laryngoscopy and intubation evoke a presser response in the human body by causing catecholamine release due to sympatho-adrenal stimulation. Various drugs have been tried to attenuate haemodynamic response to laryngoscopy and intubation during general endotracheal anaesthesia. In the last few years there has been an explosion of interest in both the physiological and pharmacological properties of magnesium and its clinical use. We planned this comparative, prospective dose response study compare the efficacy of two doses (30 mg/kg and 40 mg/kg) of intravenous magnesium sulphate in attenuating the cardiovascular response to laryngoscopy and intubation. Methods: Seventy five patients aged 15-50 years, scheduled for elective surgery under general anaesthesia, were randomly assigned to one of the three pre-treatment groups of 25 each, group C- control group, group T (MgSO4 30 mg/kg) and group F (MgSO4 40 mg/kg). Study drug was given 90-120 seconds before tracheal intubation. Heart rate, systolic blood pressure and rate pressure product were recorded at different intervals (baseline values, after study drug, after induction, at laryngoscopy, after intubation, 2 and 3 minutes after intubation). Results: Mean heart rate and systolic blood pressure was significantly high (P <0.0001) after laryngoscopy and intubation, in group C (46.87% and 40.81% from baseline) than in group T (22.78% and 7.25% from baseline) and group F (24.55% and 5.83 from baseline) respectively. Conclusions: Intravenous MgSO4 successfully attenuates the haemodynamic changes during laryngoscopy and intubation. 30 mg/kg gives adequate cardiovascular control without any complications. Transient tachycardia is more with higher doses.